Reflective Equilibrium and the Principles of Logical Analysis: Understanding the Laws of Logic - Ferreira, Acácio; Silva, Marcos (Princípios: Revista de Filosofia (UFRN), 2022)
Resenha do livro Reflective Equilibrium and the Principles of Logical Analysis de Jaroslav Peregrin e Vladimir Svoboda publicado em 2017